Pengaruh Adversity Quotient Dan Emotional Intelligence Terhadap Organizational Citizenship Behavior Karyawan Grand Rocky Hotel Bukittinggi - Yolinda Ratna Fari; Youmil Abrian; Arif Adrian (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is motivated by the importance of organizational citizenship behavior to increase productivity and effectiveness in an organization. High human fighting power will encourage the emergence of OCB behavior, namely someone who is able to survive in the face of difficulties while working will be able to carry out their obligations properly. However, according to the findings of this research conducted on employees of the Grand Rocky Hotel Bukittinggi, some employees with high OCB levels are still not able to do their jobs optimally. Therefore this research was conducted to find out whether adversity quotient and emotional intelligence affect organizational citizenship behavior of Grand Rocky Hotel Bukittinggi employees. The sample in this study were all 113 employees of the Grand Rocky Hotel Bukittinggi. Data analysis used in this study is multiple linear regression analysis. The results showed that there was a positive and significant adversity quotient with organizational citizenship behavior of employees. There is a positive and significant influence of emotional intelligence on organizational citizenship behavior of employees. Then adversity quotient and emotional intelligence both have a significant influence on organizational citizenship behavior of employees